Mast Cell Chemotaxis – Chemoattractants and Signaling Pathways - Halova, Ivana; Draberova, Lubica; Draber, Petr (Frontiers in Immunology, 2012)
Migration of mast cells is essential for their recruitment within target tissues where they play an important role in innate and adaptive immune responses. These processes rely on the ability of mast cells to recognize appropriate chemotactic stimuli and react to them by a chemotactic response. Another level of intercellular communication is attained by production of chemoattractants by activated mast cells, which results in accumulation of mast cells and other hematopoietic cells at the sites of inflammation. Mast cells express numerous surface receptors for various ligands with properties of potent chemoattractants. They include the stem cell factor recognized by c-Kit, antigen, which binds to immunoglobulin E (IgE) anchored to the high affinity IgE receptor (FcRI), highly cytokinergic IgE recognized by FcRI, lipid mediator sphingosine-1-phosphate (S1P), which binds to G-protein-coupled receptors (GPCRs). Other large groups of chemoattractants are eicosanoids [prostaglandin E2 and D2, leukotriene (LT) B4, LTD4 and LTC4, and others] and chemokines (CC, CXC, C and CX3X), which also bind to various GPCRs. Further noteworthy chemoattractants are isoforms of transforming growth factor (TGF) , which are sensitively recognized by TGF- serine/threonine type I and II  receptors, adenosine, C1q, C3a, and C5a components of the complement, 5-hydroxytryptamine, neuroendocrine peptide catestatin, interleukin-6, tumor necrosis factor- and others. Here we discuss the major types of chemoattractants recognized by mast cells, their target receptors, as well as signaling pathways they utilize. We also briefly deal with methods used for studies of mast cell chemotaxis and with ways of how these studies profited from the results obtained in other cellular systems.